A renewed focus on strengths‐based assessment in schools. (24th May 2016) - Climie, Emma; Henley, Laura
Abstract : School‐based practitioners are often called upon to provide assessment and recommendations for struggling students. These assessments often open doors to specialised services or interventions and provide opportunities for students to build competencies in areas of need. However, these assessments often fail to highlight the abilities of these students and instead focus on areas in need of remediation. The use of a more positive, or strengths‐based, approach to working with students is needed. Although strengths‐based assessment (SBA) is not a new concept, it is not routinely incorporated into school‐based assessment services. This article provides an overview of SBA and its benefits, along with empirically‐driven models that support the implementation of SBA in schools, and calls for a renewed focus on understanding students from a strengths‐based model. Examples of SBA measures and techniques are included, along with implications for practice for both students and psychologists.